Manajemen Kasus Spesialis Keperawatan Jiwa Klien Risiko Perilaku Kekerasan dengan Pendekatan Model Adaptasi Roy dan Johnsonâsbehavioral System Model Unit Intensive Rs Mm Di Bogor - Silitonga, Riris Ocktryna; Hamid, Achir Yani S.; Putri, Yossie Susanti Eka (Jurnal Keperawatan Jiwa, 2014)
People with tendency to act aggressively shown that they used destructive coping strategies to express their anger. Aim of this paper was to describe the application of Model Adaptasi Roy and Johnsonâs Behavioural System Model, focusing on aggresive behavior. Assertive training intervention that provided to 15 clients and cognitive behaviour therapy were that provided to 24 clients. Result of this study shown that sign and symptoms of aggressive behaviour were decreased and increased of clients ability to express their emotion in contructive way. Recommended the Model Adaptasi Roy and Johnsonâs Behavioural System Model with assertive training and cognitive behaviour therapy were to derecrease aggresive behaviour.